Evaluation of Diagnostic Reliability of Radionuclide Phlebography Using 99mTc-MAA to Detect Deep Venous Thrombosis; Its Role in Establishing Indications for Inferior Vena Cava Filter Implantation - Marković, S.; Odavić, M.; Matunović, A.; Raičević, B.; Prvulov, S.; Kamenica, S.; Spaić, R.; Rostovac, M.; Ajdinović, B. (Nuklearmedizin - NuclearMedicine, 1991)
Radionuclide phlebography (RNP) of the lower extremities and pelvis was performed using 99mTc-MAA in 40 patients with pulmonary thromboembolism. Deep venous thrombosis (DVT) was found in all patients, more frequently in the right calf and in the left iliac veins in 20 patients (55%). RNP and contrast phlebography (CP) were performed in 18 patients and confirmed the presence of DVT in all cases. The greatest specificity of RNP was obtained in the left (92.4%) and in the right pelvis (80%). In 12 of 18 patients in whom a cava filter was implanted, specificity of RNP was 100% for the left thigh and 91.7% for other localizations. In establishing indications for cava filter implantation, RNP should be performed prior to CP and bilaterally, but in case of non-indicated CP, RNP findings should be sufficient.Radionuklid-Phlebographien (RNP) der unteren Extremitäten und des Beckens wurden mit “Tc-MAA bei 40 Patienten mit Lungenembolie durchgeführt. Thrombosen der tiefen Venen (TVT) wurden bei allen Patienten gefunden, meistens in der rechten Wade und in den linkseitigen Iliaca-Venen bei 20 Patienten (55%). RNP und Kontrastphlebographie (KP) wurden bei 18 Patienten durchgeführt und das Vorliegen einer TVT wurde in 100% bestätigt. Die höchste Spezifität der RNP wurde im linken (92,4%) und im rechten Becken (80%) festgestellt. Bei 12 von 18 Patienten, bei denen Cava-Filter eingepflanzt worden waren, war die Spezifität der RNP 100% (linker Oberschenkel) bzw. 91,7% (andere Lokalisationen). Im Falle einer Indikation zur Einpflanzung eines Cava-Filters sollte eine RNP vor der KP und bilateral durchgeführt werden, aber im Falle von Gegenindikationen für KP reichen RNP-Befunde.